Performance and evaluation of hot mix asphalt with an addition of lime kiln dust as a mineral filler based on Western Australia conditions - Jitsangiam, P.; Nikraz, Hamid; Nusit, K. (2018)
© 2018 Trans Tech Publications, Switzerland. This study demonstrates an assessment into the different effects of lime as a mineral filler for use in densely graded hot mix asphalt (HMA). Five percent by mass of hydrated lime and lime kiln dust (LKD) were added to an asphalt mixture as its mineral filler. A series of laboratory tests to evaluate stability and flow, resilient modulus and tensile stripping ratio with reference to a control mix (a commonly used HMA) were performed. The test results showed that mixing hydrated lime into a HMA mix could enhance superior performance of hydrated lime-HMA test samples for all tests, demonstrating no moisture susceptibility. Test samples of HMA with LKD also demonstrated moisture resistance and can offer a sustainable alternative to hydrated lime, yielding one quarter of the cost. The control mix proved to be an inadequate choice upon failing the stripping potential test and therefore deemed to be susceptible to moisture.